"Our Beauty Is in Our Breasts": A Culture-Centered Approach to Understanding Cancer Perceptions in Kwa Zulu Natal, South Africa. (January 2021) - Zwane, Duduzile
Breast cancer is an incapacitating physical illness. It was once reported predominantly by patients in developed countries. With the advent of globalization, it is increasingly becoming a major health concern in developing countries such as South Africa. Breast cancer researchers have continuously advocated for original studies that address this condition from a sociocultural perspective. Consequently, in this article I examine the perceptions of breast cancer patients from underprivileged parts of Kwa Zulu Natal (KZN). Thirty semi-structured interviews were conducted with Zulu women at a tertiary hospital in the region. A culture-centered approach was utilized to gauge their perceptions of life as breast cancer patients within the conservative Zulu community. The findings revealed that this ailment is generally misunderstood, which has adverse implications for the patients. Furthermore, there is a dire need for breast cancer communication interventions that can acquaint the Zulu community with this condition.